The Analysis of the Factors Which Influence on the Subnational Units of Different Countries Participation in the Foreign Economic Relations - Elena Vasilyevna Zhiryaeva (Управленческое консультирование, 2018)
Distinctive features of subnational territories of different countries groups in the foreign economic relations are enlightened in the article. Global factors such as internationalization and markets liberalization affect everywhere. It is established that the economic crisis acts as the incentive for the external relations development in developing country because at that moment foreign trade substitutes losses in domestic market. At the periods of stable economical development there are the border territories who feel a need for external relations. Other homogeneous communities of the developing state have no certain criterion at the contractor’s choice, they follow the general political policy of the country, but the existence of just a political motivation leads to the unreasonable growth of declarative formal agreements. The slowing down process of developing countries subnational units inclusion in foreign economic relations can be explained by the insufficient enterprise activity as a main reason. Initiative like this can be generated by the regional authority if it has an attraction point in the outside world thanks to the expressed cultural and political identity. Communications of the region with special identity, even when they arise in developing country, have content and involve notable economic benefits. As far as regions usually act in the spheres of foreign investments attraction and export of small and mediumsized enterprises support, it doesn’t creates conflict with the international obligations of the nation in the peaceful world situation. This analysis is presented in comparison with a situation in the developed countries.